2011
DOI: 10.13057/biodiv/d120204
|View full text |Cite
|
Sign up to set email alerts
|

Hymenopteran parasitoids associated with the banana-skipper Erionota thrax L. (Insecta: Lepidoptera, Hesperiidae) in Java, Indonesia

Abstract: Hymenopteran parasitoids of banana-skipper Erionota thrax L. (Insecta: Lepidoptera, Hesperiidae) from Java, Indonesia are reviewed and an illustrated key to 12 species is presented to include Theronia zebra zebra, Xanthopimpla gamsura, Casinaria sp., Charops sp., Cotesia (Apanteles) erionotae, Brachymeria lasus, B. thracis, Ooencyrtus pallidipes, Anastatus sp., Pediobius erionotae, Agiommatus sumatraensis and Sympiesis sp. The surveys of the natural enemies of the banana-skipper were conducted in 1990-2006 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Parasitoid insects are natural enemies that play an essential role in BLR population control (Hasyim et al 2003;Okolle et al 2010). This study found nine species of parasitoids associated with banana skipper pests, which is quite higher than those reported previously in Indonesia (Hasyim et al 2003;Erniwati and Ubaidillah 2011;Wibowo et al 2015;Rahmawati et al 2018). The presence of P. solennis in Central Sulawesi is firstly reported by this study.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Parasitoid insects are natural enemies that play an essential role in BLR population control (Hasyim et al 2003;Okolle et al 2010). This study found nine species of parasitoids associated with banana skipper pests, which is quite higher than those reported previously in Indonesia (Hasyim et al 2003;Erniwati and Ubaidillah 2011;Wibowo et al 2015;Rahmawati et al 2018). The presence of P. solennis in Central Sulawesi is firstly reported by this study.…”
Section: Discussioncontrasting
confidence: 64%
“…In this study, we investigated the incidence and parasitism of BLR at different elevates and banana cultivars. Previous studies have been reported the BLR attack on bananas in Indonesia and other tropical countries (Hasyim et al 1994;Hasyim et al 1999;Erniwati and Ubaidillah 2011;Irulandi et al 2018). It is generally known that BLR attacks do not significantly reduce banana production except in high attack rates (Okolle et al 2006).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…M. manilae was known as a polyphagous parasitoid that attacks armyworm Spodoptera litura, the most important insect pest of many agricultural crops in Indonesia (Shepard, Barrion, & Litsinger, 1987). B. lasus was a gregarious endoparasitoid predator of the banana leaf roller Erionota thrax (Erniawati & Ubaidillah, 2011). The polyphagous egg parasitoid Trichogramma is one of around 80 genera from the family Trichogrammatidae, that has been most used as biocontrol agents in agricultural crops (Cônsoli & Grenier, 2009).…”
Section: Screening For Wolbachia Infection In Several Parasitic Insectsmentioning
confidence: 99%